How do you find f^-1(x) given f(x)=2x+7?

2 Answers

f^-1(x)=1/2(y-7)

Explanation:

Given:
f(x)=2x+7

Let y=f(x)

y=2x+7

Expressing x in terms of y gives us the inverse of x

y-7=2x

2x=y-7

x=1/2(y-7)

Thus,

f^-1(x)=1/2(y-7)

Mar 3, 2018

The f^{-1} notation indicates you need to find the inverse of the function

Explanation:

There are a couple of ways to look at function inverses. An inverse of anything allows you to 'undo' whatever you started with. So, if you tie your shoe, it's not there forever - you can always untie it.

We have many inverse functions in math, such as square root is the inverse of squaring a number, etc.

Finding the inverse also reflects the graph across the line y = x.

There are 3 steps to finding an inverse:

1) change notation f(x) = to y =

So, y = 2x + 7

2) Exchange the x & y variables. Note this is what accomplishes that reflection across the line y = x

So, x = 2y + 7

3) Since x is the dependent variable and y is the independent variable and it is always a zillion times easier to solve a problem in y = form, solve the equation for y.

First subtract 7 from both sides

x - 7 = 2y

Then divide by 2

y = {x-7}/2